1978
DOI: 10.3382/ps.0570804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diflubenzuron (Dimilin; TH—6040) on the Hyaluronic Acid Concentration in Chicken Combs ,

Abstract: The addition of N-[[(4-chlorphenyl)amino]carbonyl]-2,6-difluorobenzamide(diflubenzuron; Dimilin; TH-6040) up to levels of 250 ppm of the total diet of both male broilers and layers for 98 days did not affect the hyaluronic acid (HA) concentration (microgram/g tissue) in the combs. The concentration was measured at 21, 28, 42, 56, and 98 days on feed. The concentration in the combs of the layers were not significantly different at any sampling period regardless of diet. At the end of 56 days on feed, the combs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…29 Feeding diflubenzuron to growing chickens at the same levels did not affect body, testes, liver, comb, and feet weights. No significant effects on body weight gain, egg production, fertility, and hatchability were observed 30 -31 when two breeds of laying hens were fed 10|xg/g diflubenzuron for 15 weeks.…”
Section: Farm Animals Birds and Arthropodsmentioning
confidence: 95%
“…29 Feeding diflubenzuron to growing chickens at the same levels did not affect body, testes, liver, comb, and feet weights. No significant effects on body weight gain, egg production, fertility, and hatchability were observed 30 -31 when two breeds of laying hens were fed 10|xg/g diflubenzuron for 15 weeks.…”
Section: Farm Animals Birds and Arthropodsmentioning
confidence: 95%
“…The chitin synthesis inhibitors include the benzoylureas, diflubenzuron, lufenuron and hexaflumuron and a chemically different compound, buprofezin. Diflubenzuron, the most studied compound of the group, does not appear to inhibit hexosamine transferases, which are required for glycosaminoglycan formation in vertebrates 42–45. The acute toxicity of the benzoylureas is low, while the repeated‐dose toxicity in experimental animals is dominated by effects on the blood, probably mediated through aniline metabolites (see the review by Marrs46).…”
Section: Insecticides Targeting Structures In Insects That Are Not Fomentioning
confidence: 99%
“…Miller et al (1976) observed no significant effects on body weight gain, egg production, fertility, or hatchability when two breeds of laying hens were fed 10 ppm diflubenzuron for 15 weeks. Crookshank et al (1978) showed that feeding diflubenzuron for 98 days at levels up to 250 ppm did not affect the hyaluronic acid content of combs of male broiler or layer chickens. There is not adequate information in the literature on the effects of diflubenzuron ingestion by poultry.…”
Section: Introductionmentioning
confidence: 98%